If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 4) + 6 = 38 Reorder the terms: 8(4 + x) + 6 = 38 (4 * 8 + x * 8) + 6 = 38 (32 + 8x) + 6 = 38 Reorder the terms: 32 + 6 + 8x = 38 Combine like terms: 32 + 6 = 38 38 + 8x = 38 Add '-38' to each side of the equation. 38 + -38 + 8x = 38 + -38 Combine like terms: 38 + -38 = 0 0 + 8x = 38 + -38 8x = 38 + -38 Combine like terms: 38 + -38 = 0 8x = 0 Solving 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '8'. x = 0 Simplifying x = 0
| -24+3k=k-2k | | (4x^2)+16x+13=0 | | 13.7v-6.5=-2.3+8.3 | | n^2=-5n | | 2(x+4)-5x+7= | | 0=-6(y+2) | | 5=4(x-2)+9 | | 7+6x=-4(x-5)+7 | | 12-1.2(x-5)=22-2(x-4) | | -4(t+6)=4 | | -3-8x+5x=4-4x | | n^2+6n=-5 | | 3k+8k=8k-9 | | 5(x-7)+2=-28 | | 3x+5=3(x-9) | | -5(z+7)=-6z | | x*2-x=12 | | 5n-4(n-6)=2+2n | | 10-(3y-3)=2-4y | | x/8-1=-5 | | 2x*2-x=45 | | 3xy^2-2xy+2=-3y^2+y+4x | | 10-4(x-5)=11-x | | 4v^2-4v=15v | | h=4f | | x^2-20x=-53 | | -4x-9+3(2x+5)-2= | | (-7x+2)-(-6x-5)=3 | | 12(t-2)+6t=6(3t+3)-12 | | 3b=11b | | 7[3-(8x-3)]+4x=0 | | 3x^2+10x-32=0 |